Roridomyces phyllostachydis (Agaricales, Mycenaceae), a new bioluminescent fungus from Northeast India - Karunarathna, Samantha C.; Mortimer, Peter E.; Tibpromma, Saowaluck; Dutta, Arun Kumar; Paloi, Soumitra; Hu, Yuwei; Baurah, Gautam; Axford, Stephen; Marciniak, Catherine; Luangharn, Thatsanee; Madawala, Sumedha; Lin, Chang; et al. (Phytotaxa, 2020)
An interesting bioluminescent fungus growing on dead bamboo stems was collected from bamboo forests in the East Khasi and West Jayantia Hills Districts of Meghalaya, Northeast India. Both morphological characteristics and phylogenetic analyses of nrITS and nrLSU regions showed that the bioluminescent fungus belongs to the genus Roridomyces and is a new species to science, as well as the first report of the genus, Roridomyces, in India. Full descriptions, colour photographs, phylogenetic trees to show the position of the novel bioluminescent taxon, and comparisons with its morphologically and phylogenetically similar species are provided.